168k views
4 votes
2x - 3y = -5
5x - 22 = -4y

Solve In Multiplication Method

1 Answer

5 votes

Answer:

(2, 3 )

Explanation:

Given the 2 equations

2x - 3y = - 5 → (1)

5x + 4y = 22 → (2) [ rearranged equation ]

Multiplying (1) by 4 and (2) by 3 and adding will eliminate the term in y

8x - 12y = - 20 → (3)

15x + 12y = 66 → (4)

Add (3) and (4) term by term to eliminate y, that is

23x = 46 ( divide both sides by 23 )

x = 2

Substitute x = 2 in either of the 2 equations and evaluate for y

Substituting into (2)

5)2) + 4y = 22

10 + 4y = 22 ( subtract 10 from both sides )

4y = 12 ( divide both sides by 4 )

y = 3

Solution is (2, 3 )

User Pcurry
by
6.9k points